Neonatal adrenal insufficiency: Turkish Neonatal and Pediatric Endocrinology and Diabetes Societies consensus report - Yiğit, Şule (Turk Pediatri Ars, 2018)
It is difficult to make a diagnosis of adrenal insufficiency in the newborn, because the clinical findings are not specific and the normal serum cortisol level is far lower compared to children and adults. However, dehydratation, hyperpigmentation, hypoglycemia, hyponatremia, hyperkalemia and metabolic acidosis should suggest the diagnosis of adrenal insufficiency. Hypotension which does not respond to vasopressors should especially be considered a warning. If the adrenocorticotropin hormone level measured simultaneously with a low serum cortisol level is 2-fold higher than the upper normal limit of the reference range, a diagnosis of primary adrenal insufficiency is definite. Even if the serum cortisol level is normal, a diagnosis of relative adrenal insufficiency can be made with clinical findings, if the patient is under heavy stress. The serum cortisol level should be measured using the method of ‘high pressure liquid chromatography’ or ‘LC mass spectrometry’. Adrenal steroid biosynthesis can be evaluated more specifically and sensitively with ‘steroid profiling’. Rennin and aldosterone levels may be measured in addition to serum electrolytes for the diagnosis of mineralocorticoid insufficiency. Adrenocorticotropic hormone stimulation test may be used to confirm the diagnosis and elucidate the etiology. In suspicious cases, treatment can be initiated without waiting for the adrenocorticotropic hormone stimulation test. In schock which does not respond to vasopressors, intravenous hydrocortisone at a dose of 50-100 mg/m(2) or a glucocorticoid drug at an equivalent dose should be initiated. In maintanence treatment, the physiological secretion rate of hydrocortisone is 6 mg/m(2)/day (15 mg/m(2)/day in the newborn). The replacement dose should be adjusted with clinical follow-up and by monitoring growth rate, weight gain and blood pressure. Fludrocortisone (0,1 mg tablet) is given for mineralocorticoid treatment (2x0,5-1 tablets). A higher dose may be needed in the neonatal period and in patients with aldosterone resistance. If hyponatremia persists, oral NACl may be added to treatment. In the long-term follow-up, patients should carry an identification card and the glucocorticoid dose should be increased 3-10-fold in cases of stress.